Replication strategy of human hepatitis B virus. - Will, H (1987)
To study the replication strategy of the human hepatitis B virus, the 5' end of the RNA pregenome and the initiation sites of DNA plus and minus strands have been mapped. The RNA pregenome was found to be terminally redundant by 120 nucleotides; it is initiated within the pre-C region and may also function as mRNA for synthesis of the major core protein and the hepatitis B virus reverse transcriptase. The hepatitis B virus DNA minus strand is initiated within the direct repeat sequence DR1, it contains a terminal redundancy of up to eight nucleotides, and its synthesis does not require any template switch. The DNA plus strand is primed by a short oligoribonucleotide probably derived from the 5' end of the RNA pregenome, and its synthesis is initiated close to the direct repeat sequence DR2. For its elongation to pass the discontinuity in the DNA minus strand an intramolecular template switch occurs using the terminal redundancy of this template. Thus, the route of reverse transcription and DNA replication of hepatitis B viruses is fundamentally different from that of retroviruses.